The Comparison of Fluid Dynamics Parameters in an Andersen Cascade Impactor Equipped With and Without a Preseparator - Dechraksa, Janwit (Springer US, 2014)
The fluid dynamic data in Andersen cascade impactor (ACI) are still lacking. Airflows and those affected parameters can be predicted in a preseparator and Andersen cascade impactor (ACI) by computational modeling. This study developed a validated computational fluid dynamic (CFD) model of an ACI and investigated the effects of the preseparator on the CFD parameters. Validation of the computational nozzle velocity for each of the stage 0 to stage 5 of the ACI stages was found to be within a 3.56% error. The flow field indicated that the preseparator accelerated the airflow velocity at the induction tube from 1.13 to 3.71 ± 0.09 m/s and 2.40 to 8.68 ± 0.16 m/s (at 28.3 and 60 L/min of flow rate, respectively). The preseparator produced a nozzle's wall shear stress ranged from 0.08 to 0.34 Pa on a collection plate, while the ex-preseparator spread wall shear from the plate's center was in a range of 0.11 to 0.37 Pa (at 28.3 L/min of flow rate). Moreover, the nozzle velocities increased along the distance from the middle of the collection plate to the periphery. The CFD explained the airflow of the preseparator equipped model by accelerating the airflow along the inlet port to maximize the trapping of desirable particles and the generation of a smooth wall shear stress at the collection plate to reduce the particle re-entrainment. While, the ex-preseparator generated an airflow that resulted in a higher wall shear stress occurring on the lower stages.